2002
DOI: 10.4049/jimmunol.169.8.4136
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility to T Cell-Mediated Injury in Immune Complex Disease Is Linked to Local Activation of Renin-Angiotensin System: The Role of NF-AT Pathway

Abstract: FcR provides a critical link between ligands and effector cells in immune complex diseases. Emerging evidence reveals that angiotensin (Ang)II exerts a wide variety of cellular effects and contributes to the pathogenesis of inflammatory diseases. In anti-glomerular basement membrane Ab-induced glomerulonephritis (GN), we have previously noted that FcR-deficient mice (γ−/−) surviving from lethal initial damage still developed mesangial proliferative GN, which was drastically prevented by an AngII type 1 recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 69 publications
(85 reference statements)
3
41
0
1
Order By: Relevance
“…2, a and b). CD4 ϩ T cell-dependent injury, characterized by mesangial proliferation as described in our recent study (34), was not induced at this dose of NTS in ␥ Ϫ/Ϫ mice. At 5 wk after BM transplantation (day 0), the genotypes of peripheral blood in W␥ and ␥W chimeras were replaced with that of WT or ␥ Ϫ/Ϫ mice, respectively (Figs.…”
Section: Bm-derived Cells Expressing Fcr Play a Crucial Role In The Imentioning
confidence: 83%
“…2, a and b). CD4 ϩ T cell-dependent injury, characterized by mesangial proliferation as described in our recent study (34), was not induced at this dose of NTS in ␥ Ϫ/Ϫ mice. At 5 wk after BM transplantation (day 0), the genotypes of peripheral blood in W␥ and ␥W chimeras were replaced with that of WT or ␥ Ϫ/Ϫ mice, respectively (Figs.…”
Section: Bm-derived Cells Expressing Fcr Play a Crucial Role In The Imentioning
confidence: 83%
“…For example, AngII participates in the recruitment of inflammatory cells to a site of injury by direct actions on infiltrating cells and via regulation of expression of adhesion molecules, cytokines, and chemokines (12,36,37). In this study, large numbers of ED-1-positive mononuclear cells were observed in the kidneys of control SHR.…”
Section: Discussionmentioning
confidence: 99%
“…Sequences of the FIRE S1 and S2 double-stranded oligonucleotides (ds-oligos) used for the EMSAs are presented (Fig. 2A); a cognate NFAT site from the mouse IL-2 enhancer (IL-NFAT) served as a positive control (32). As shown in Fig.…”
Section: The Downstream Half Of Fire Is Sufficient To Confer Fast Musclementioning
confidence: 99%